2003
DOI: 10.1002/ajim.10170
|View full text |Cite
|
Sign up to set email alerts
|

Health care utilization of carpenters with substance abuse‐related diagnoses

Abstract: These findings support the need for alcohol and drug abuse prevention and treatment services for this workforce. Operationalizing this among highly mobile workforces, such as the construction trades, is a challenge. While not intending to minimize the problems of alcohol or substance abuse on the job among carpenters, the focus of prevention should not necessarily be in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The consumption index [Gordon et al, 2001] used in the present study was intended to detect grades of hazardous alcohol use. We found no major difference in the present-day alcohol consumption between the trades studied; also carpenters can be at risk of alcohol abuse [Lipscomb et al, 2003]. The subject selection criteria probably excluded some cases of severe abuse; all subjects had to be employed presently, or at least during the past year, and in occupation for more than 1 year.…”
Section: Discussionmentioning
confidence: 98%
“…The consumption index [Gordon et al, 2001] used in the present study was intended to detect grades of hazardous alcohol use. We found no major difference in the present-day alcohol consumption between the trades studied; also carpenters can be at risk of alcohol abuse [Lipscomb et al, 2003]. The subject selection criteria probably excluded some cases of severe abuse; all subjects had to be employed presently, or at least during the past year, and in occupation for more than 1 year.…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have documented high rates of smoking, alcohol, and other substance use in the construction trades (68). While overall smoking rates have declined in recent years, there continues to be a substantial disparity among different occupational groups (9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…One would expect former heavy drinkers to be more likely to have health‐related problems and hence more healthcare use than abstainers. Studies that demonstrated an increase in healthcare use with increased quantities and frequencies of alcohol use involved individuals drinking alcohol at subsyndromal levels (lacking at least one symptom of abuse or dependence) (Salome, French, Matzger, & Weisner, 2005), at abuse or dependency levels (Lipscomb, Dement, & Li, 2003), or with comorbid psychiatric problems (Mertens, Weisner, Ray, Fireman, & Walsh, 2005). Thus, while drinking 5+ drinks/day is, by itself, a red flag for potential problems, the 5+ drinks/day marker alone does not necessarily translate into healthcare use.…”
Section: Discussionmentioning
confidence: 99%